Using Andersen’s Behavioral Model of Health Care Utilization to Assess Contraceptive Use among Sexually Active Perinatally HIV-Infected Adolescents in Uganda - Mbalinda, Scovia N.; Kaye, Dan K.; Nyashanu, Mathew; Kiwanuka, Noah (International Journal of Reproductive Medicine, 2020)
Background. Contraceptive practices of perinatally HIV-infected adolescents (PHIAs) have implications related to pregnancy prevention, risks of HIV heterosexual transmission, reinfection, and vertical transmission. The study assessed contraceptive use among sexually active PHIAs in Uganda. Methods. Mixed methods consisting of a survey and in-depth interviews were employed among 213 sexually active PHIAs who were attending antiretroviral therapy (ART) clinics. The study was guided by Andersen’s Behavioral Model of Health Service Use as a theoretical framework to identify factors that influence contraceptive use. These factors include health care factors, personal characteristics, enabling factors, and needs. The outcome was contraceptive use. Multivariable logistic regression was used to establish determinants of contraceptive use. Qualitative data were analyzed by thematic analysis. Results. Most PHIAs were female (67.6%); the mean (SD) and median (IQR) age was 17.5 (±1.4) and 18 (17-19) years. The mean age of sexual debut and at marriage were 15 (±1.7) and 17 (±1.1), respectively. Condoms were the most known method of family planning (indicated by 55.4%). Only 16.9% of the participants knew about dual protection (condom use for FP as well as HIV/STI prevention). Of the PHIAs, 43.6% had ever used modern contraception and 56.9% of the females had ever been pregnant. The odds of contraceptive ever-use were significantly higher among adolescents aged 17-19 years (OR 5.1, 95% CI: 2.1-13.3) compared to those aged 10-16 years, those in school (OR 1.8, 95% CI: 1.07-3.2) compared to those out of school, and those with perceived need to use FP (OR 2.0, 95% CI: 1.1-3.9) compared to their counterparts. The odds of contraceptive used were lower among females (OR 0.13, 95% CI: 0.06-0.28) compared to males. From the in-depth interviews, the attitude of health workers, availability of health workers, having a friend using family planning, and waiting time were viewed to affect contraceptive use. Conclusion. Contraceptive use among sexually active perinatally HIV-infected adolescents was (43.6%). However, out of those who used family planning majority were using short-term methods. The unmet need for family planning was high (47%) with high reports of pregnancy (56.9%). The factors associated with contraceptive use included education, age, sex (predisposing factors), and perceived need of family planning (need factors). Other factors that could affect contraceptive use from qualitative analysis included attitude of health workers, availability of health workers, having a friend using family planning (predisposing factors), and waiting time (health system factors). HIV care for adolescents should be promoted using SRH approach. There is a need to provide training for all providers to cater for SRH services. We should continue to provide youth-responsive adolescent sexual and reproductive health services across all ART facilities and build a supportive environment and continue to integrate SRH services into HIV care.